Eating and cooking loss characteristics of electrically stimulated and hot boned bull inside round muscle chilled at different rates - S.D. Shivas; Curtis L. Kastner; Michael E. Dikeman; Melvin C. Hunt; Donald H. Kropf (Kansas Agricultural Experiment Station Research Reports, 1983)
We found steaks cut from inside rounds (chilled fast or slow) of electrically stimulated and hot boned bull carcasses, to be similar to conventionally processed steaks in taste panel, shear force and cooking loss characteristics.
Keywords: Cattlemen' s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Electrically stimulated; Hot boned; Chiling